2010
DOI: 10.1007/s12665-010-0470-1
|View full text |Cite
|
Sign up to set email alerts
|

Speleogenesis and deposition of sediments in Cioclovina Uscată Cave, Sureanu Mountains, Romania

Abstract: The sedimentary deposits from Cioclovina Uscatȃ Cave yielded numerous paleontological, anthropological and mineralogical findings. However, until now, a study of the sediments and their depositional features and environment had not been conducted. Here, we present a complete study of the sediments within the Main Gallery with the purpose of documenting their origin, depositional mode and processes, and direction of the paleodrainages. Seventeen sedimentary profiles were mapped and analyzed. A complete map was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Likewise, a well-organised channelised underground conduit network (e.g., Piccini, 2011;Martini, 2011;Bella et al, 2021) is needed to generate the sedimentary structures observed. Most Chalk caves and conduit systems, both in the Caumont system, and in other Chalk caves in Normandy and elsewhere (Laignel et al, 2004;Rodet et al, 2006;Stenestad, 2006;Willems et al, 2007;Dobrowolski et al, 2012;Chédeville et al, 2015;Grube et al, 2017), are typically infilled with fine-grained sediments rather than the coarse allogenic sediments often seen in limestone caves (e.g., Häuselmann et al, 2010;Arriolabengoa et al, 2020). This reflects the small size of the allogenic catchments, the dominance of sand and clay-rich cover materials, notably loessic deposits and the Clay-with-Flint (Chédeville et al, 2015), the low hydraulic gradients in Chalk areas (Fournier et al, 2007(Fournier et al, , 2008Sanz et al, 2016), and the typically small nature of the conduits limiting sediment transport in the Chalk aquifer.…”
Section: Detrital Sedimentation In Chalk Cavesmentioning
confidence: 99%
“…Likewise, a well-organised channelised underground conduit network (e.g., Piccini, 2011;Martini, 2011;Bella et al, 2021) is needed to generate the sedimentary structures observed. Most Chalk caves and conduit systems, both in the Caumont system, and in other Chalk caves in Normandy and elsewhere (Laignel et al, 2004;Rodet et al, 2006;Stenestad, 2006;Willems et al, 2007;Dobrowolski et al, 2012;Chédeville et al, 2015;Grube et al, 2017), are typically infilled with fine-grained sediments rather than the coarse allogenic sediments often seen in limestone caves (e.g., Häuselmann et al, 2010;Arriolabengoa et al, 2020). This reflects the small size of the allogenic catchments, the dominance of sand and clay-rich cover materials, notably loessic deposits and the Clay-with-Flint (Chédeville et al, 2015), the low hydraulic gradients in Chalk areas (Fournier et al, 2007(Fournier et al, , 2008Sanz et al, 2016), and the typically small nature of the conduits limiting sediment transport in the Chalk aquifer.…”
Section: Detrital Sedimentation In Chalk Cavesmentioning
confidence: 99%
“…The Southern Carpathians host sites with extensive cave deposits (speleothems, sediments and fossil remains) of high importance both as palaeoclimate archives and as repositories of anatomically modern humans remains (Riel-Salvatore et al 2008;Häuselmann et al 2010;Doboș et al 2010;Fu et al 2015Fu et al , 2016. Muierilor Cave holds an impressive Marine Isotope Stage 3 (MIS 3) fossil assemblage (Doboș et al 2010) as well as sedimentological and mineralogical features relevant for the regional geological evolution during the Quaternary (Diaconu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Their merit resides in their applicability to a variety of connected research fields: anthropology and archaeology (e.g., Berger et al, 2008), paleoclimatology (e.g., Audra et al, 2007;Polk et al, 2007), paleoenvironment and paleotopography reconstructions, mineralogy (e.g., Polyak and Guven, 2000;Onac et al, 2007), sedimentology and speleogenesis (e.g., Horoi, 1993;Roată, 1993;Häuselmann et al, 2010), as well as several others (e.g., Sasowsky, 2007).…”
Section: Introductionmentioning
confidence: 99%